Familiar Distance. Picture Postcards from Java from a European Perspective, ca. 1880–1930 - Sophie Junge (BMGN: Low Countries Historical Review, 2019)
This paper examines the cross-imperial production and reception of picture postcards from the Dutch East Indies. As travelling agents of colonial knowledge, picture postcards helped to circulate and promote the political demands of the Dutch colonial empire. At the same time, the layout and the iconography of these postcards expressed contemporary visual standards and fulfilled European expectations of a successfully governed colony in Southeast Asia. With the focus on one particular set of postcards that was sent from Java’s largest harbour city Soerabaja (present-day Surabaya) to the Swiss entrepreneur Adolf Feller in Switzerland in 1924, this paper follows the practices of making, buying, sending and receiving these postcards. The analysis reconstructs the cross-imperial business initiatives by diverse actors from the Netherlands and of Chinese heritage in Soerabaja, from Armenia, England and Switzerland and shows how Swiss individuals participated and supported Dutch colonial propaganda as part of a European culture of colonialism.